Upaya Meningkatkan Kompetensi Guru Kelas dalam Proses Pembelajaran Melalui Supervisi Akademik di SD Negeri 4 Mataram - Andria Suginam (Universitas Pendidikan Mandalika, 2019)
he purpose of this study was to determine the effectiveness of the implementation of academic supervision in an effort to improve the competence of classroom teachers in the learning process. This research method uses classroom action research conducted in two cycles, each cycle of activities there are four stages namely planning, implementation, observation, and reflection. The results of this study indicate that; 1) the results of the observation of the principal and observations of the teacher during the mentoring process have obtained an average score of> 4.0, 2) the final result> 85% of the total number of mentoring participants received an average grade of> 75.00 (good category). The results of the study in the first cycle observation of the average principal (3.40), average teacher observation (3.33) and the academic supervision results of the average grade teacher (64.82). In cycle II the average headmasters observation (4.70) with the percentage of achievement (100%), the average teacher observation (4.67) with the percentage of achievement (83.33%) and the results of academic supervision in the target (language teacher english) average grade (85.96) with percentage of achievement (100%). Indicators of success have been achieved, the research was declared successful and stopped in the second cycle.